Study on the Impact of Intercultural Education and the Technological Revolution on Sustainable Education - Albulescu, Ion; Manea, Adriana Denisa; Stan, Cristian (Social Welfare: Interdisciplinary Approach, 2025)
The quality education of young people in formal institutionalized frameworks is achieved only by connecting to the socio-cultural reality, while adapting to the transformations/changes caused by technological developments. Our study aims to investigate the perception of current and future teachers for primary and preschool education regarding the role and impact of the digital revolution on the achievement of quality educational actions and the influence of intercultural education in the economy of a sustainable education. The study was conducted on a sample of 354 students of the Faculty of Psychology and Educational Sciences, Babeș-Bolyai University, Cluj-Napoca, Romania, majoring in Primary and Preschool Education Pedagogy. The investigation revealed the dependence relationship between the level of digital skills and their school/professional performance. At the same time, quality education is associated with intercultural education.
Keywords: qualitative education; intercultural education; digital skills; technological developments